The Influece of Self Help Group on Self Esteem of New Students - Sari, Monica Kopda; Fitrianur, Widya Lita; Suminar, Ervi; Zuhroh, Diah Fauziah (Universitas Muhammadiyah Gresik, 2024)
New students need to adapt to a new environment because of the differences between high school and university education. One therapeutic therapy to maintain mental or emotional health is the Self Help Group (SHG). The purpose of this research is to determine the effect of self help groups (SHG) on the self-esteem of new students of the Nursing Science Study Program, Muhammadiyah University of Gresik. This research uses a One Group PreTest – PostTest design. The population of this study were 43 new students of the Nursing Science Study Program at Muhammadiyah University of Gresik using the Total Sampling sampling technique. Researchers used Self Help Group therapy as the independent variable and self-esteem as the dependent variable. The instruments in this research used the RSES questionnaire and observation sheets. Statistical tests using Mc Nemar, research results before being given self-help group (SHG) therapy showed that almost all students had high self-esteem, 37 (86%) and after being given self-help group therapy, all students had high self-esteem, 43 (100%) . The Mc Nemar statistical test results obtained p = 0.031 so p < a 0.05. So it is known that there is an influence of the Self Help Group on the self-esteem of new students of the Nursing Science Study Program, Muhammadiyah University of Gresik, so it is hoped that this therapy can be applied at the University.